2015
DOI: 10.15376/biores.11.1.519-529
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Modification of Microcrystalline Cellulose by Grafting Copolymerization

Abstract: Microcrystalline cellulose (MCC) has the advantage of a high specific surface area as compared to that of conventional cellulose fibers. In this study the monomer methacrylamide (MAM) was used to treat MCC by grafting copolymerization. SEM, FTIR, and solid 13 C NMR were used to characterize the morphology and composition of MAM-g-MCC. After the chlorination of MAM-g-MCC with 10% sodium hypochlorite solution, the grafted MCC exhibited antibacterial activity as a result of the formation of N-Cl bonds. The therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, the surface area of those antibiotic films will be much lower than our catalytic NIPS membrane or electrospun web. Although there are few numbers of papers describing high stability of N‐Cl at high concentration, we cannot obtain enough stability at high concentration with large surface area . These results will be, again, the reason why the detoxification efficiency of nanofiber web is much lower than that of NIPS membrane.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, the surface area of those antibiotic films will be much lower than our catalytic NIPS membrane or electrospun web. Although there are few numbers of papers describing high stability of N‐Cl at high concentration, we cannot obtain enough stability at high concentration with large surface area . These results will be, again, the reason why the detoxification efficiency of nanofiber web is much lower than that of NIPS membrane.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, the electron‐donating methyl groups on hydantoin can help to stabilize N‐Cl form . Several researches have also paid their attention on the stability of N‐Cl as described in Supporting Information 1 . Based on the previous literature, the N‐Cl groups seem to be quite stable and have long enough shelter time before usage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the volume expansion of paraffin–stearic acid, paraffin–palmitic acid, and stearic–myristic acid PCM mixtures were equal to 12%, 12%, and 10%, respectively. Li et al . used PEG as a PCM and modified wood as porous media in their preliminary studies.…”
Section: Introductionmentioning
confidence: 99%